Adapting to change: facing the challenges in developing ESL students' communicative competence - Abd Rahman, Siti Nadhirah; Razali, Abu Bakar (Universiti Putra Malaysia, 2024)
Developing students’ communicative competence during the pandemic is not an easy task, especially with the abrupt shift to remote learning. This study is intended to explore the challenges faced by English as a Second Language (ESL) instructors in developing students’ communicative competence in an online classroom. This study involves three ESL instructors in a university, as well as three students from each instructor’s class. The chosen data collection methods were in-depth interviews and stimulated recall for the ESL instructors and focus group discussions for the students. The findings show that among the challenges faced by ESL instructors include the lack of student engagement and socialisation, the fact that the course was designed for physical classes, and the lack of access to high-speed internet. The students also shared their experiences when faced with these issues. It is hoped that ESL teachers, course developers and administrators can understand the issues faced by ESL instructors with remote learning to develop students’ communicative competence.